White Women, U.S. Popular Culture, and Narratives of Addiction. (September 2018) - Daniels, Jessie; Netherland, Julie C.; Lyons, Alyssa Patricia
The United States war on drugs has, for decades now, systematically targeted communities of color. This sustained attack on people of color is accomplished through the use of whiteness. Recently, mainstream news media and elected officials have called for a "gentler war on drugs" to address the opioid epidemic. While some may see this as a welcome change, we take a more critical view. Specifically, we examine the role of White women in two popular television series that feature narratives of addiction as a gendered instance of "white drug exceptionalism." To do this, we conducted a systematic analysis of a narrative television show, Law & Order, and a reality-based show, Intervention, using nine seasons over the same time period (2000–2010). In the procedural drama Law & Order, White women were featured prominently as part of the carceral state, both as police detectives and as prosecutors. Occasionally, White women are portrayed as victims of drug culture. On the rehabinspired Intervention, the majority of all characters are White, and the audience is invited to view drug use and recovery through a white lens that tells a particular kind of story about addiction. Both the carceral model promoted by Law & Order and the therapeutic model valorized by Intervention rely on particular notions of White womanhood mapped onto neoliberal regimes of citizenship that not only compel us all toward "health" and "sobriety" but also warp our collective imagination, so that we only see some drug users as worthy of a gentleness and compassion.